Involvement of cigarette smoke-induced epithelial cell ferroptosis in COPD pathogenesis - Masahiro Yoshida (Nature Portfolio, 2019)
Altered iron homeostasis resulting in excessive oxidative stress has been implicated in smoke-induced lung diseases. Here the authors show that ferroptosis of lung epithelial cells, potentially resulting from excessive ferritinophagy, is involved in the pathogenesis of COPD.